Pengaruh Pengetahuan Pajak, Modernisasi, dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Tingkat Pendidikan sebagai Variabel Moderator - Sindhi Sindhi; Kasih Purwantini (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to examine the factors influencing individual taxpayer compliance by highlighting the role of tax knowledge, administrative system updates, and the frequency of outreach. The frequent failure to achieve state budget revenue targets underscores the importance of delving into current taxpayer behavior. Using explanatory quantitative methods, this study collected data through an online questionnaire from 96 productive-age respondents (18–55 years old) in Demak Regency. In addition to examining the direct influence of these three factors, the study also considered education level as a moderating variable. The analysis showed that understanding the rules, ease of use of the new system, and intensive outreach significantly increased taxpayer compliance. Furthermore, education level was found to strengthen this relationship; individuals with a strong academic background were more likely to adapt to digital systems such as e-filling and e-billing. In conclusion, legal awareness and technological proficiency are born from a solid educational foundation. Therefore, the synergy between community-based education and the provision of an easily understood digital system is key to building long-term tax compliance..